2012
DOI: 10.1016/j.cbpra.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Attention: Implications for Understanding and Treating Internalizing and Externalizing Disorders in Childhood

Abstract: In this article, we present evidence that disorders of attention are present in wide range of psychological disorders, and that the appropriate assessment and treatment of these attention difficulties can be an important adjunct to traditional therapeutic approaches. We review approaches to attention training in some detail and discuss how attention-focused treatment might be implemented in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
3
24
1
Order By: Relevance
“…At the same time, however, other research has reported no differences in planning performance between such participants with BPD and healthy controls (Kunert, Druecke, Sass & Herpertz, 2003). Furthermore, current data suggest that association between BPD and planning deficits may be more modest in magnitude than the large effects that were indicated at the time of Ruocco's (2005) review.…”
Section: Are Specific Domains Of Executive Function Key Markers For Bpd?contrasting
confidence: 57%
See 4 more Smart Citations
“…At the same time, however, other research has reported no differences in planning performance between such participants with BPD and healthy controls (Kunert, Druecke, Sass & Herpertz, 2003). Furthermore, current data suggest that association between BPD and planning deficits may be more modest in magnitude than the large effects that were indicated at the time of Ruocco's (2005) review.…”
Section: Are Specific Domains Of Executive Function Key Markers For Bpd?contrasting
confidence: 57%
“…Research into the neurocognitive underpinnings of BPD has grown considerably in recent decades and has associated the disorder with a range of deficits (Ruocco, 2005). Although this research has provided much evidence that self-regulatory dysfunction and impulsivity are core to BPD, questions regarding the specific cognitive domains in which self-regulatory deficits are located remain largely unresolved.…”
Section: Is Bpd Characterized By Executive Function Deficits?mentioning
confidence: 99%
See 3 more Smart Citations